The market driven organization : - Day, George S. (Free Press, 1999)
Market Driven Strategy is a buzzword that many business people use without grasping its full meaning. This text offers practical advice for managers who want to better communicate with their customers, perform miles ahead of their competitors, and continually be responsive to both.